A Novel Range Free Visible Light Positioning Algorithm for Imaging Receivers - Soto-Gomez, J; Seguel-Gonzalez, F (Elsevier GmbH, 2019)
In this paper a novel 2-D range free visible light positioning algorithm for imaging receivers is presented. Its performance is obtained by computational simulation. For doing this, an heterogeneous visible light communications network inside a room of dimensions 3 × 3 ×3 m is modelled in MATLAB. A receiver s height localization interest zone between 1 and 1.5 m is considered for simulation. Moreover, different field of view angles at the receiver side ranging from 40° to 120° are used in order to measure the behaviour of our proposed algorithm to changes on detector parameters. Optimal detector architecture that minimizes the error of position estimation is identified and used as case of study. Our method overcomes the traditional convex position estimation (CPE) in terms of accuracy, in all proposed scenarios. The combination of convex polygon positioning (CPP) method and imaging detectors at the receiver side increases the accuracy of position estimation and, robustness to changes in receiver s height. Field of view angles have low impact on method performance when four photodetectors are used. Effect of mismatches in height measurement, tilting and rotation angles is also analysed. © 2019 Elsevier GmbH